Neoplatonic and Gnostic Resonances in the Martyrdom of Cyprian of Athenais Eudocia - Dendrinos, Markos; Griva, Anna (Dia-noesis: A Journal of Philosophy, 2024)
Aelia Eudocia Augusta (formerly Athenais), wife of the emperor Theodosius II, lives at the borderline between the ancient and the Christian world and writes one of the most distinctive poetic texts of Byzantine literature. In the Martyrdom of Cyprian, written in Homeric language, the Saint's past, when he was a magician and initiated into a multitude of Greek mysteries, is presented in an original and remarkable way. Within this text, the resonance of philosophical ideas originating from Neoplatonism and Gnosticism is of particular interest. This article attempts to highlight these resonances in order to open a research dialogue regarding the complex network of ideas and the coexistence of different worldviews in early Byzantium.